2012
DOI: 10.1016/j.ijsu.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-term results of modified Karydakis flap and modified Limberg flap for pilonidal sinus surgery

Abstract: The aim of this study was to compare and analyze the short term results of modified Karydakis flap reconstruction (MKF) and modified Limberg flap reconstruction (MLF). This is a retrospective analysis of 81 patients operated for pilonidal sinus disease. There were 46 patients in MLF group and 35 patients in MKF group. We compared patients age, BMI, operation time, removal time of suction drain, time of feeling completely healed, type of presentation, complications, postoperative 1., 3., 5. Days VAS scores, tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 26 publications
6
30
0
2
Order By: Relevance
“…Karaca et al reported 5.7% recurrence and 22.9% complication rate. 9 As similar in this study, the recurrence rate was 4.1% and the complication rate was 12,2% in the MKF group.…”
Section: Resultssupporting
confidence: 84%
“…Karaca et al reported 5.7% recurrence and 22.9% complication rate. 9 As similar in this study, the recurrence rate was 4.1% and the complication rate was 12,2% in the MKF group.…”
Section: Resultssupporting
confidence: 84%
“…The same study further found no significant difference between the groups in terms of full healing time. 22 In their prospective randomized study, Ertan et al found that Limberg flap is advantageous compared with primary repair in terms of painless walking and return-to-work time; whereas they did not find any significant difference between the groups in terms of painless toilet-sitting time and hospital stay. 18 In their prospective randomized study on 269 patients, Ates et al found that Limberg flap is superior to Karydakis flap in terms of operation time and hospital stay time; on the other hand they did not find any significant difference between the groups in terms of time of return to normal activity, and postop pain.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, the lengths of hospital stay in the LF and the KF groups were 1.48 ± 0.50 and 1.41 ± 0.49 days, respectively. Karaca et al [29] reported that the lengths of hospital stay were 1.1 and 1 days for the Limberg and the Karydakis flap surgeries, respectively. In a study by Bali et al [23], the durations of hospital stay were 1 and 2 days in the LF and the KF groups, respectively.…”
Section: Discussionmentioning
confidence: 99%